PERLINDUNGAN HUKUM TERHADAP PIHAK KREDITUR AKIBAT RISIKO KREDIT DALAM TRANSAKSI FINTECHT BERBASIS P2P LENDING - Tommy Leonard; Natasia Sitompul; July Esther; Willy Tanjaya (LPPM Universitas Ekasakti Padang, 2023)
The type of fintech peer-to-peer lending that has experienced the most growth in Indonesia is a type of financial technology that allows customers to get loans with simple, easy and fast procedures and does not require them to have collateral. But in reality, this fintech presents a very high credit risk. This is due to the efforts of fintech companies. as a coordinator when other financial institutions' standards are not met when evaluating buyers. Consequently, there is a need for preventive legal prescriptions and protection, especially for lenders. This is managed in the Financial Services Authority regulation Number.77.01.2016 regarding the implementation of information technology-based money lending and the Financial Services Authority regulation Number.1.07.2013 regarding Consumer Protection in the Financial Services Sector. Both of these regulations can be found on the official website of the Financial Services Authority (OJK). Lenders have sufficient legal protection thanks to these two POJKs, but additional legal protection is needed, particularly in the area of ​​credit risk reduction.